ANÁLISIS DE LOS ESTADOS FINANCIEROS DE LA COOPERATIVA DE AHORRO Y CRÉDITO “LAS LAGUNAS” DEL CANTÓN SARAGURO, PERIODOS: 2016-2018, PROPUESTA DE MEJORA - Saca Paqui, María Magdalena (2019)
The present work called: ANALYSIS OF THE FINANCIAL STATEMENTS OF THE COOPERATIVE OF SAVINGS AND CREDIT "LAS LAGUNAS" OF SARAGURO CANTON, PERIODS: 2016-2018, PROPOSAL OF IMPROVEMENT was developed with the purpose of determining the economic-financial situation of the organization and At the same time, identify their protection, asset quality, performance rates, liquidity and signs of growth. The methodology used to develop the objectives set out in the financial analysis began with the collection of information provided by the cooperative's manager, followed by the first objective through vertical and horizontal analysis where it was known that the The organization in 2018 has assets of $ 1,170,416.15, being financed with 72.49% of liabilities and with 27.51% of assets. The horizontal analysis showed a sustained growth of the asset of 26.16% for the year 2018 in relation to the previous year, in terms of liabilities it presents an increase of 35.38%, which is justified by the increase in deposits with the public, while in equity it increased 6.79% due to the increase in share capital. By applying the PERLAS indicators, it could be determined that the cooperative has provisioned 100% of its overdue portfolio> 12 months; the level of protection or liquidity for the savings and contributions of its members, in the case of liquidation of the assets and liabilities the cooperative is in the capacity to meet the demand for withdrawals. However, there are weak areas such as: delinquency of the credit portfolio, low level of public deposits, high percentages of unproductive assets and low profitability. In relation to the second objective, it was determined that at the equilibrium point, the cooperative must have an income greater than or equal to $ 157,782.63, using 96.01% of its installed capacity and thus not generate losses. Concerning the cash conversion cycle, this is converted every 38 days, where the average collection period is 54 days and the payment period of the obligations with the public is 16 days, with recovery days being longer than payment days. which means that the cooperative must have external funds until the recovery of the portfolio. In the third objective, according to the shortcomings found, four improvement proposals were proposed, such as: setting incentives to stimulate savings and attract new partners; reduce the rate of unproductive assets; adequate administration of Credit Portfolio; and increase profitability, in order to contribute with alternative solutions to the problems identified in the research, helping to improve their economic stability and quality of service.